STAT3 Knockdown Induces Tumor Formation by MDA-MB-231 Cells - Banerjee, Kasturi (Clin Oncol Res, 2018)
STAT3 plays a central role in oncogenesis by mediating cell survival, growth, and differentiation. It is constitutively activated in breast cancer. We investigated the role of STAT3 in tumor development by knocking down STAT3 levels in MDA-MB-231 triple negative breast cancer cells using short hairpin RNA. The tumor forming potential of these STAT3-depleted cells was assessed by xenografts in immunocompromised NOD SCID mice. Contrary to its accepted tumor promoting role, we found STAT3 to be a negative regulator of growth in MDA-MB-231- derived tumors. Although similar observations have been made in thyroid carcinoma and lung adenocarcinoma xenograft studies, our novel results showed for the first time that the role of STAT3 in promoting tumorigenesis may be context-specific, and that STAT3 may actually be a negative regulator of certain breast-cancer types. Studies to identify the mechanisms of STAT3’s negative regulatory role may be useful in developing STAT3-based therapeutics.